WWOX and Its Binding Proteins in Neurodegeneration - Hsu, Che-Yu (Cells, 2021)
WW domain-containing oxidoreductase (WWOX) is known as one of the risk factors for Alzheimer’s disease (AD), a neurodegenerative disease. WWOX binds Tau via its C-terminal SDR domain and interacts with Tau phosphorylating enzymes ERK, JNK, and GSK-3β, and thereby limits AD progression. Loss of WWOX in newborns leads to severe neural diseases and early death. Gradual loss of WWOX protein in the hippocampus and cortex starting from middle age may slowly induce aggregation of a protein cascade that ultimately causes accumulation of extracellular amyloid beta plaques and intracellular tau tangles, along with reduction in inhibitory GABAergic interneurons, in AD patients over 70 years old. Age-related increases in pS14-WWOX accumulation in the brain promotes neuronal degeneration. Suppression of Ser14 phosphorylation by a small peptide Zfra leads to enhanced protein degradation, reduction in NF-κB-mediated inflammation, and restoration of memory loss in triple transgenic mice for AD. Intriguingly, tumor suppressors p53 and WWOX may counteract each other in vivo, which leads to upregulation of AD-related protein aggregation in the brain and lung. WWOX has numerous binding proteins. We reported that the stronger the binding between WWOX and its partners, the better the suppression of cancer growth and reduction in inflammation. In this regard, the stronger complex formation between WWOX and partners may provide a better blockade of AD progression. In this review, we describe whether and how WWOX and partner proteins control inflammatory response and protein aggregation and thereby limit AD progression.